A career exploration program for junior high students with learning disabilities - Power, Kimberly Ann, 1969- (2001)
Thesis (M.Ed.)--Memorial University of Newfoundland, 2001. -- Education Bibliography: leaves 64-71. -- Internet access available to MUN users only.